Empathetic Attitudes and Violence Management Skills in Nursing Students: Relationships and Outcomes - Aktura, Seher Çevik; Çelik, Hanife (My University, 2025)
Objective: The study aimed to examine the relationship between empathic tendency and violence management competence in clinical practice among nursing students. Materials and Method: This correlational study was conducted among nursing students enrolled in the spring semester of the 2024-2025 academic year at a university in the eastern region of Türkiye between March 2024 and June 2024. The study population consisted of nursing students (N=812) enrolled in the spring semester in academic year. The sample size was determined to be 287 students using OpenEpi version 3 \"Sample Size Calculation for a Known Population\" with an effect size of 80% and a confidence interval of 95%. Data were collected using a personal information form, the Empathic Tendency Scale and the Violence Management Competence Scale for Nursing Students in Clinical Practice. Results: The study found that the mean score of nursing students on the Clinical Violence Management Skills Scale was 93.72 ± 27.03 (28, 140), while the mean score on the Empathic Tendency Scale was 65.12 ± 8.52 (41, 91). A weak but statistically significant positive correlation was observed between the mean score on the Empathic Tendency Scale and both the overall mean score and the sub-dimensions of the Violence Management Competence Scale (P<0.001, P<0.05). Conclusion: The study concluded that nursing students have above-average levels of empathic tendency and violence management competence in clinical practice. It was observed that as students' empathic tendencies increased, their competence in managing violence in clinical settings also improved.
Keywords: Clinical practice; Empathetic tendency; Nursing stundent; Violence management